Amicus Curiae Briefs and the U.S. Supreme Court: When Liberal and Conservative Groups Support the Same Party. (2nd April 2016) - Swenson, Karen
Abstract: I examine patterns of amicus curiae participation before the U.S. Supreme Court for six terms, OT2007–OT2012. I explore the interesting phenomenon of liberal and conservative group participation on the same side of a case, and I hypothesize that when this occurs, the Court is more likely to vote in favor of the party supported by these groups. I control for the impact of other factors that may influence the Court to side with a party, including the party is the U.S.; the U.S. appears as amicus curiae for that party; number of amicus briefs on behalf of the party relative to its opponent; and the ideological direction of the decision in the court below that is on appeal to the U.S. Supreme Court.